(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
Homicide-suicide episodes are complex phenomenon and multidimensional events associated with the additive or multiplicative effects of many circumstances, including psychopathological, psychosocial, economical, cultural or environmental stress. The present case is being reported with an attempt to evaluate the episode so that preventive measures could be adopted.